25. VALUE OF MEAN PLATELET VOLUME INDEX IN PREDICTING THE CAUSE OF THROMBOCYTOPENIA (Vietnam Journal of Community Medicine, 2025)
Objective: Studying on the value of the mean platelet volume index in predicting the cause of thrombocytopenia in patients treatmented at Military Hospital 103.Subjects  and  methods: A cross sectional study was done on 192 patients with thrombocytopenia treated at the Field Internal Medicine Center, Military Hospital 103 between October 2019 and October 2024. They were split into two groups: 86 patients with underproductive bone marrow and 106 patients with over-destruction of platelets, and a control group of 110 healthy volunteers.Results: The average value of mean platelet volume index in over-destruction of platelets group was statistically significantly higher than that of the underproductive bone marrow group and the control group, with p < 0.0001. The cut-off value of mean platelet volume index in predicting the cause of thrombocytopenia was 10.25 fL and the area under the curve AUC = 0.68 and p < 0.0001. The sensitivity and specificity of the mean platelet volume index in predicting the cause of thrombocytopenia were 52.8% and 84.9%, respectively.Conclusions: The mean platelet volume index should be considered as a screening tool for early prediction of the cause of thrombocytopenia.
Keywords: Mean platelet volume; underproductive bone marrow of platelets; over-destruction of platelets.